A DEVELOPMENT OF PRACTICUM INSTRUCTIONS BASED ON RESEARCH UTILIZATION OF MICROORGANISM IN BIOTECHNOLOGY MATERIALS IN MAKING TEMPE, TAPE AND YOGURT - Nila Kartika Sari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
Developing practicum manual based on the results of research on the use of microorganisms in the use of microorganisms on biotechnology materials in making tempe, tape and yogurt to help students in practicum activities so that their activities are directed. The development method used is a development research method that refers to the 4D model which has four stages namely: 1) Define, 2) Design, 3) Develop, and 4) Disseminate the stages used in the development of this practical guide book until the 3RD stage, namely the develop stage. Based on the preliminary test and questionnaire analysis of the needs of 45 students in the 2016 Biology class, that so far students have not used the practice manual based on the results of research into the use of microorganisms in making tempe, tape and yogurt on Biotechnology material. The results of the validation of expert Mate and media expert both reached 81% of material experts, and 85% of media experts, with very valid criteria. So it can be concluded that the development of practical guide books based on the results of research into the use of microorganisms in making tempe, tape and yogurt on biotechnology materials is feasible and can be used in practical learning takes place.